Synthesis of a Chiral Auxiliary Family from Levoglucosenone and Evaluation in the Diels–Alder Reaction - Klepp, Julian; Sumby, Christopher J.; Greatrex, Ben W. (Synlett, 2018)
A new family of chiral auxiliaries has been developed based on the lignocellulosic biomass pyrolysis product levoglucosenone. A promising single stereoisomer with an alcohol and π-stacking phenyl substituents was prepared in excellent yield in two steps from dihydrolevoglucosenone without chromatography on >50 g scale. Acrylate esters prepared from the auxiliaries underwent diastereoselective Lewis acid promoted Diels–Alder reactions with cyclopentadiene (endo/exo 98:2, endo d.r. up to 98:2), dimethylbutadiene (d.r. 93:7), and isoprene (d.r. > 98:2)
Keywords: chiral auxiliary; chiral pool; levoglucosenone; Diels–Alder reaction; diastereoselectivity